2020 12th International Conference on Computational Intelligence and Communication Networks (CICN) 2020
DOI: 10.1109/cicn49253.2020.9242597
|View full text |Cite
|
Sign up to set email alerts
|

Webinars: An assistive tool used by higher education educators during Covid19 case study

Abstract: The education ecosystem in India is primarily dependent on face to face interaction of teachers with students. Technology assistive tools available to educators act as an aid for imparting quality education. However, the complete transition from face-to-face interaction to virtual interaction was challenging for educators over the world during the Covid-19 pandemic outbreak. This paradigm shift in teaching and the use of webinars as the primary resource for teaching has shown a significant impact on the learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Por otro lado, Kumar et al (2020) presentan un trabajo relacionado con las herramientas de asistencia tecnológica que están disponibles para que se pueda impartir una educación de calidad en entornos en línea. Particularmente, se enfocan en los Seminarios Web (Webinars) como herramienta de enseñanza para que los profesores puedan llevar a cabo sus clases durante este período de COVID-19.…”
Section: Introductionunclassified
“…Por otro lado, Kumar et al (2020) presentan un trabajo relacionado con las herramientas de asistencia tecnológica que están disponibles para que se pueda impartir una educación de calidad en entornos en línea. Particularmente, se enfocan en los Seminarios Web (Webinars) como herramienta de enseñanza para que los profesores puedan llevar a cabo sus clases durante este período de COVID-19.…”
Section: Introductionunclassified
“…In terms of rankings, the following data is revealed. The usefulness of webinars as a teachinglearning activity was established in previous studies (Kumar, et al, 2020;Yo et al, 2021aYo et al, , 2021b, which could help explain why the code "Gratefulness" (142) to the organizers obtained the highest rank. It is followed by "Greeting" (116).…”
Section: Evaluation Based On the Facebook Commentsmentioning
confidence: 91%
“…Chin (2020) found that 36.9% out of 900000 students cannot follow the online classes due to lack of facilities needed for online learning. Kumar et. al (2020) found that out of 38 respondents, 7 or 18% of the respondents didn't have online learning tools.…”
Section: Problem Statementmentioning
confidence: 99%